The Effect Of Using The Savi (Somatic, Auditory, Visualizing, And Intellectual) Method Toward Writing Skills Across Gender - Muhammad Riko Yohansyah Zulfahmi; Veni Roza (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study was to examine the significant effects across genders of the use of the Somatic Auditory Visual Intellectual (SAVI) on the writing of students in SMA Negeri 1 Payakumbuh District. The sample was two classes of 52 students, an experimental class XI IPS 2 taught using SAVI and a control class XI IPS 4 taught by a conventional model (Teacher Center). Each class consisted of two groups based on gender (male and female). The data were then analyzed using the ANOVA test. Before running the ANOVA test, we performed assumption tests, i.e., normality and homogeneity tests. Here are the results of this study:(1) SAVI is more effective than traditional models. (2) Female students have better writing skills than male students. (3) There is a correlation between teaching methods and students using SAVI in writing instruction. English teachers are therefore encouraged to use SAVI in writing classes. This method positively contributes to improving the student’s writing skills.